Analisis Pemahaman Matematis Siswa Ditinjau dari Gaya Kognitif Reflektif-Impulsif - Styoningtyas Bety; Mirza Hariastuti Rachmaniah (FPMIPA IKIP PGRI Bali, 2020)
Mathematical understanding is one's ability to absorb and convey mathematical ideas again. Mathematical understanding can be influenced by the way a person has in receiving, absorbing, and relaying the information received. To achieve the objectives, the research employs descriptive qualitative research to find out students' mathematical understanding of polynomial material in terms of Reflective-Impulsive cognitive style. The method by collecting data is consist of tests, interviews, and documentation. The data obtained were analyzed qualitatively based on indicators that have been determined. The results showed that the Mathematical understanding of subjects with Reflective cognitive style was good. In this research is shown by the fulfillment of Mathematical understanding indicators, the students can: (1) identify and make examples and not examples; (2) translating and interpreting symbol meanings and mathematical sentences; (3) understand and apply mathematical ideas; and (4) make an extrapolation. Whereas mathematically the subjects with Impulsive cognitive style are still not good. This is indicated by the fact that almost all indicators have not been fulfilled.